Toward Light‐Regulated Living Biomaterials. Issue 8 (29th June 2018) - Sankaran, Shrikrishnan; Zhao, Shifang; Muth, Christina; Paez, Julieta; del Campo, Aránzazu
Abstract: Living materials are an emergent material class, infused with the productive, adaptive, and regenerative properties of living organisms. Property regulation in living materials requires encoding responsive units in the living components to allow external manipulation of their function. Here, an optoregulated Escherichia coli (E. coli) ‐based living biomaterial that can be externally addressed using light to interact with mammalian cells is demonstrated. This is achieved by using a photoactivatable inducer of gene expression and bacterial surface display technology to present an integrin‐specific miniprotein on the outer membrane of an endotoxin‐free E. coli strain. Hydrogel surfaces functionalized with the bacteria can expose cell adhesive molecules upon in situ light‐activation, and trigger cell adhesion. Surface immobilized bacteria are able to deliver a fluorescent protein to the mammalian cells with which they are interacting, indicating the potential of such a bacterial material to deliver molecules to cells in a targeted manner. Abstract : A light‐activatable living biointerface is developed by combining optogenetics and bacterial surface display in an endotoxin‐free Escherichia coli (E. coli) system. Mammalian cells specifically interact with surface‐immobilized E. coli displaying adhesive miniprotein on their outermembranes in response to light. The in situ delivery of protein from E. coli to the mammalian cells is also observed.